Early Cardiac Changes in Radioiodine Treated Young Athyrotic Patients Receiving Thyroid Stimulating Hormone (TSH) Suppressive Levothyroxine (LT4) Replacement - Begum, Fatima; Ahmed, Chaudhury Meshkat; Kabir, Enamul; Nahar, Nurun; Sultana, Sadia; Banerjee, Sajal; Afroz, Shahana; Zaman, Nazma (Bangladesh Journal of Nuclear Medicine, 2017)
Objective: The objective of this study was to evaluate early changes of heart due to thyroid stimulating hormone (TSH) suppressive levothyroxine (LT4) replacement in young athyrotic patients with differentiated thyroid carcinoma (DTC). Materials and Methods: Thirty young athyrotic patients with DTC, age ranged 20-39 years after radioactive iodine ablation therapy (RAIT), were selected prospectively. These patients had been receiving 200µg/day LT4 replacement therapy starting from the third day of RAIT. Age, sex, body mass index (BMI), body surface area (BSA) and life style matched 23 healthy volunteers were recruited in the study. Clinical, thyroid hormones levels and Doppler Echocardiographic and Tissue Doppler Imaging (TDI) data were taken at baseline at two months of initiation of LT4 replacement in patients with DTC and in healthy volunteers. Echocardiographic data of patients with DTC were repeated at second visit after 6-12 months of RAIT and both data compared with control. Results: Diastolic parameters evaluated by Doppler Echocardiography and TDI were significantly different in patients with DTC compared to control. Early diastolic tissue velocity (Em) in patients with DTC showed higher value at second visit compared to control (Em, control subjects, 19±6 cm /sec, patients at second visit, 23 ± 4 cm /sec, p<0.03). Late diastolic flow (Am) of patients was higher at two visits (Am, at first visit, 15±5 cm/sec; at second visit, 19 ± 6 cm/sec) (p<0.004) compared to control (Am, 9 ± 1.6 cm/sec). Modified Tei index was significantly increased (mean 0.48 ± 0.06) in second visit in patients with DTC compared to control (mean 0.33 ± 0.04) and at first visit (mean 0.31 ± 0.05, p<0.001) respectively. Conclusion: It is concluded that supraphysiologic dose of LT4 has side effects on heart even within short period of replacement. TDI is an important tool to evaluate the early changes in myocardium. Bangladesh J. Nuclear Med. 18(1): 9-15, January 2015